2020
DOI: 10.1002/jsid.918
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the color capability of modern display systems

Abstract: Historically displays used three colorants in an additive system. During that time, the CIE chromaticity diagram adequately illustrated color capability. Modern displays are not constrained by this additive architecture, and the diagram can fail in its purpose. This is demonstrated by analysis and a large number of display measurements. A device‐independent methodology using CIE 1976 L*a*b* color gamut volume is described that provides a robust means to determine the size of the color gamut. This methodology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…For example, if the display is known to reproduce only five image levels, then it will be sufficient to subdivide the input colour into a 5 × 5 grid. The CIELAB color gamut envelope is derived from the measured colors that were uniformly sampled from the surface of the RGB signal cube, and the volume determined through tessellation 10,14,18 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, if the display is known to reproduce only five image levels, then it will be sufficient to subdivide the input colour into a 5 × 5 grid. The CIELAB color gamut envelope is derived from the measured colors that were uniformly sampled from the surface of the RGB signal cube, and the volume determined through tessellation 10,14,18 …”
Section: Methodsmentioning
confidence: 99%
“…Recent research on emissive displays demonstrated that a display that can produce colors over a wider range of luminance may yield a larger color gamut volume, but not necessarily a larger chromaticity area. 13,14 However, it is important not to interpret this as color quality perceived by a human observer. The gamut volume is only one measure of color capability, the capability of a display to produce a range of colors in CIELAB.…”
Section: Objective and Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…As reinforced in recent publications, 3,4 and as explained in the new IDMS (section 21.3.2), color gamut is a volume ∗. It is critical to use three‐dimensional tools that consider the lightness axis, in addition to chromaticity, to properly represent any display's color capability.…”
Section: Color Metrologymentioning
confidence: 99%